Swahili personality-trait vocabulary: A psycho-lexical study using dictionary and day-to-day conversations by indigenous speakers - Harrun H. Garrashi; Boele De Raad; Dick P.H. Barelds (International Journal of Personality Psychology, 2024)
Human social behavior is a function of peoples’ personalities and individual differences. As humans engage in social behaviors, peoples’ traits and other unique attributes come out and get noticed, and community members may feel tempted to talk about these attributes and either encourage them or discourage them: words are created and they become part of the community’s lexicon. In this study we employed the psycho-lexical approach to hunt for those words that describe people’s traits and unique attributes and that have thus become encoded in the lexicon, in particular of the Swahili language, an eastern Africa Bantu language. We used two resources for this purpose, (1) a Swahili dictionary, as the tangible repository of the lexicon, and (2) free descriptions. As a final result we concluded that the trait vocabulary of the Swahili language contains a useful set of 1,338 trait terms, of which 4% are adjectives, 55% are nouns, and 41% are verbs. Thus, nouns form the largest number of trait terms, followed by verbs, while adjectives occupy an insignificant third position in the Swahili trait vocabulary.